Identification of gaps to conduct a study on biological self-healing concrete - Talaiekhozan, Amirreza (2013)
Biological self-healing concrete is a new idea to have concrete structures with more durability. Although, several papers have been published on biological self-healing concrete, a suitable instruction to conduct this type of studies is not reported. Aim of this paper is collecting comprehensive information about conducting a study on self-healing concretes based on previous studies. This paper present many new ideas that have not been completely study. Some idea such as application of fungi, thermopiles bacteria, mix culture of microorganisms or using of aerobic or anaerobic bacteria to design biological selfhealing concrete are suggested in this paper. Ideas of this paper can help researchers to find a suitable and novel subject in biological self-healing area to conduct a strong research.